Geometric dimensioning and tolerancing applications in hard disk drive industry - Ngoh, Peng Huat. (2008)
In this dissertation, the applications of Geometric Dimensioning and Tolerancing (GD&T) on a Hard Disk Drive (HDD) are illustrated and studied using various examples. These examples show how GD&T helps to improve the performance of HDD in terms of storage capacity, speed and reliability. Different GD&T families are applied in these examples. Each of the GD&T families and their unique characteristics and benefits in applications are discussed. The main objective of this dissertation is to illustrate the concepts of GD&T through applications in HDD industry. The aids of real life industry case studies give a better understanding of GD&T usage. Hence, GD&T knowledge would be more appreciated. But, if GD&T are incorrectly applied, it will confuse the machinists or the inspectors of the product. This will result in lost of production time and higher cost incurred due to scraps and reworks. Thus, the product lost its market competitiveness. Hence, thorough understanding of GD&T is essential in HDD industry.